2016
DOI: 10.35790/ebm.4.2.2016.13998
|View full text |Cite
|
Sign up to set email alerts
|

Kecacingan usus pada anak sekolah dasar di Tanawangko Kecamatan Tombariri Kabupaten Minahasa

Abstract: Helminth is one of the most commonly infected parasites in human. According to WHO, more than 1,5 billions of people around the world are infected by helminthes. The highest number of helminthiasis cases is of school age children. This study was aimed to obtain the helminthiasis cases in students of elementary schools at Tanawangko Minahasa and to identify the types of helmiths. This was a descriptive study. Feces samples from the students were kept in feces pot and then were examined microscopically. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Intestinal worms infect most often people who have poor hygiene and sanitation, especially children who lack an understanding of how to live a clean and healthy life. In addition, the density between people's residences, geographical conditions, and climate play an important role in the transmission of intestinal worms (Luis et al, 2016) Community service is carried out for one year, starting from January-December 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal worms infect most often people who have poor hygiene and sanitation, especially children who lack an understanding of how to live a clean and healthy life. In addition, the density between people's residences, geographical conditions, and climate play an important role in the transmission of intestinal worms (Luis et al, 2016) Community service is carried out for one year, starting from January-December 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of parasitic infection in coastal area were reported by a study in Tanawangko, Tombariri Sub-district, Minahasa District found that 4.3% elementary school children were infected with Ascaris lumbricoides 7 . Another study conducted in coastal area of Wori Sub-district, North Minahasa District showed that 4.7% children suffered from intestinal helminth infections and 15.5% children were infected with with intestinal protozoa.…”
Section: Abstrakmentioning
confidence: 99%